Effect of provenance on flowering behaviour of parental lines of sunflower (Helianthus annuus L.) Hybrid-KBSH-78: Effect of provenance on flowering behaviour of parental lines of sunflower (Helianthus annuus L.) Hybrid-KBSH-78 - T M RAMANAPPA; C K PRAMILA; M S UMA; S D NEHRU (Journal of Oilseeds Research, 2023)
The study revealed that sowing of parental lines of sunflower hybrid KBSH-78 at different locations had no significant influence on plant growth specially flowering behaviour and seed yield. However, 50% flowering was observed at 57 DAS in male parent and 62 DAS in female parent i.e., female parent is late in 50% flowering by 5 days compared to male parent. In order to achieve the better synchronization between parental lines and also to enhance seed yield of the seed parent, male parent has to be sown late with two staggered sowings of 3rd and 5th day after sowing of female parent, irrespective of the seed production locations.